Socio-symbolic ownership: extending the socio-emotional wealth perspective. (21st November 2016) - Nordqvist, Mattias
Abstract : Purpose: The purpose of this paper is to extend the socio-emotional wealth (SEW) perspective in general, and the contribution by Martin and Gomez-Mejia (this issue) in particular. The aim is also to address recent calls to incorporate more micro-level theorizing in the development of the SEW perspective and to embrace the rich, real-world environment in which this phenomenon takes place. Focus is particularly on the SEW dimension that is related to the ability to exercise family control over a business. Design/methodology/approach: The approach is conceptual and introduces symbolic interactionism, a theory from micro-sociology and socio-psychology, to the SEW literature within the family business field. The paper draws on a previously published study by the author and relies on the centrality of the notion of socio-symbolic ownership in family firms. Findings: The concepts of socio-symbolic ownership and the process of enacting ownership underline how family and non-family actors interpret and act upon specific guiding values and interests that constitute SEW at a micro level in each family firm. Socio-symbolic ownership and the guiding values and interests that the ownership is based on allow scholars to capture SEW differences among family firms, as the specific values and interests typically vary between family firms. Originality/value: An approach is outlined that helps scholars to develop a more process-sensitive theory of SEW. Studying how and why actors engage in the social interactions, symbolic relations and interpretations that constitute the decision-making gives a better understanding of the important micro-foundations of SEW, and of the heterogeneity of family firms.